The new home : a handbook for tenants (London : The Health and Cleanliness Council, 1937)
1937 1937 1930s 24 pages : illustrations SHOPPING WISELY IS GETTING GOOD VALUE FOR MONEY See that you buy from clean shops, where the assistants are clean and have clean habits, and where dogs and other animals are not allowed to run over the premises. See that there is no blowing into paper bags which hold your cakes, and see that your food is wrapped in clean paper. Don't buy disease with your food. Make sure your bread is handled and delivered in a clean manner. [illustration] Buy your food in clean shops. [insert] Modern equipment is the housewife's blessing — but whether you're up-to-date or out-of-date, be clean! Never leave the fire without its guard if there are children about. It is not safe. THE BEDROOMS KEEP BEDROOMS AS AIRY AS POSSIBLE The bedroom windows should be open as much as possible during the night and should be opened wide as soon as the occupants are up in the morning. BEDS WILL BE MORE COMFORTABLE IF THEY ARE WELL LOOKED AFTER The bed should be stripped on rising. Children should be taught to do this and to leave the mattress to air — it should be turned every day. Dust can best be removed by an electric vacuum cleaner from [illustration] Put beds to air. 11 177/5/8/2